1999
DOI: 10.1007/s11661-999-0269-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of martensite content and morphology on tensile and impact properties of high-martensite dual-phase steels

Abstract: A series of dual-phase (DP) steels containing finely dispersed martensite with different volume fractions of martensite (V m ) were produced by intermediate quenching of a boron-and vanadiumcontaining microalloyed steel. The volume fraction of martensite was varied from 0.3 to 0.8 by changing the intercritical annealing temperature. The tensile and impact properties of these steels were studied and compared to those of step-quenched steels, which showed banded microstructures. The experimental results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
196
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 353 publications
(206 citation statements)
references
References 30 publications
9
196
1
Order By: Relevance
“…They relate this to the martensite phase becoming softer as its volume fraction increases. Other authors (Bag et al (1999)) show that softening of the aggregate occurs at v,,, ~ 0.55 and not V,II = 0.3 and this explains why they get three distinct regions ev en though they used VIII> 0.3. The difference is thought to be due to different alloying and morphology used in each investigation.…”
Section: 5mentioning
confidence: 91%
See 2 more Smart Citations
“…They relate this to the martensite phase becoming softer as its volume fraction increases. Other authors (Bag et al (1999)) show that softening of the aggregate occurs at v,,, ~ 0.55 and not V,II = 0.3 and this explains why they get three distinct regions ev en though they used VIII> 0.3. The difference is thought to be due to different alloying and morphology used in each investigation.…”
Section: 5mentioning
confidence: 91%
“…Increasing the volume fraction of the harder phase was found to increase the yield and ultimate strengths of the aggregate. Bag et al (1999) reported that the increase in strength with v'll only extends up to v'll ~ 55% after which a reduction in strength is observed. The same was observed by Byun and Kim (1993) but at a different value of VIII ' Shen, Lei and Liu (1986) have observed this as weIl without specifying the value of VIII at which this takes place.…”
Section: Mechanics Of Deformation Of Dp-steelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 5 shows Vickers micro-hardness values for α and β phases from which 0.2% offset yield strength of the samples is calculated using the rule of mixtures 2 The work hardening behaviour is analysed using the modified Crussard -Jaoul (C-J) model [59][60][61][62][63], as the samples contain two phases similar to dual phase steel for which this model was developed. The modified C-J model uses the following Eq.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…It is mentioned in [61][62]72] that three stages in the work hardening behaviour depend upon the amount and type of the constituents present in the microstructure. Stage I corresponds to the plastic deformation of β phase that work hardens due to the glide of dislocations and formation of pile ups in the vicinity of the hard α phase grains which serve as barriers to dislocation motion and initially do not deform plastically.…”
Section: Mechanical Propertiesmentioning
confidence: 99%